The Influence of Intellectual Capital and Working Capital Management on Financial Distress and its Impact on Stock Returns - Ambarawati, Ni Made Siti; Yuniarta, Gede Adi; Werastuti, Desak Nyoman Sri (Amkop Management Accounting Review (AMAR), 2025)
This study aims to empirically prove the influence of intellectual capital and working capital management on stock returns of technology sector companies listed on the Indonesia Stock Exchange through financial distress. The population in this study consisted of technology sector companies listed on the Indonesia Stock Exchange in 2021-2023, totaling 29 units. The number of samples was determined using a purposive sampling technique to obtain 24 companies that met the criteria. Data analysis used SEM (Structural Equation Modeling) assisted by Stata 14 software. The results of the study showed that intellectual capital and working capital management had a negative effect on financial distress, intellectual capital and working capital management did not affect stock returns, financial distress had a negative effect on stock returns, intellectual capital and working capital management positively affected the stock returns of technology sector companies listed on the Indonesia Stock Exchange in 2021-2023 through financial distress.